Morphological and ecological-biological features of the spontaneous hybrid Acer platanoides L. × A. truncatum Bunge - O. I. Fedorinova; B. L. Kozlovskiy; M. V. Kuropyatnikov (Acta Biologica Sibirica, 2019)
The article gives a description of the spontaneous hybrid Acer platanoides L. × A. truncatum, Bunge revealed during introductions research in the Botanical Garden of SFedU. The prerequisite for the emergence of closely related hybrids was the use of the method of genus complexes in the creation of a collection. Interspecies hybrids are detected in polymorphic genera: Acer, Berberis, Corylus, Crataegus, Lonicera, Sorbus. The economic interest is represented by a spontaneous hybrid A. platanoides × A. truncatum. The following are given: morphological description of the hybrid and parental species, their basic ecological and biological properties (winter hardiness, drought resistance, resistance to diseases and pests, seeds reproductive capacity), seasonal development rhythm, characteristics of seeds and decorative qualities.